The Influence of Health Education on Blood Sugar Levels and Foot Care Behavior in Diabetes Mellitus Patients - Situmeang, Dewi M S; Prabawati, Dewi (Griya Eka Sejahtera, 2025)
Background: Diabetes mellitus (DM) is a long-term illness that needs serious care and can cause significant problems, such as sores on the feet. Good knowledge and behavior regarding foot care can prevent and delay potential complications. Therefore, health education regarding foot care is crucial for DM patients. This study aimed to analyse the effect of health education on blood sugar levels and foot care behavior in diabetes mellitus patients.Methods: This study used a literature review approach using the PRISMA protocol. The article search strategy and research questions were formulated using the PICO framework in the initial stage. Google Scholar, Garuda, and SINTA databases were used for the book search. Data analysis was conducted qualitatively.Results: Health education effectively improves knowledge and foot care behavior in patients with DM. This can, in turn, prevent complications such as diabetic ulcers and improve foot care behavior (daily inspection, hygiene, footwear selection, and early help-seeking) in people with diabetes mellitus.Conclusion: Health education has been proven effective in improving knowledge and foot care behavior in diabetes mellitus patients, which can prevent complications such as diabetic ulcers.